Study on coinfecting vector-borne pathogens in dogs and ticks in Rio Grande do Norte, Brazil - Gonçalves, Luiz Ricardo [UNESP]; Filgueira, Kilder Dantas; Ahid, Silvia Maria Mendes; Pereira, Josivânia Soares; Vale, André Mendes do; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
Since dogs presenting several vector borne diseases can show none or nonspecific clinical signs depending on the phase of infection, the assessment of the particular agents involved is mandatory. The present study aimed to investigate the presence of Babesia spp., Ehrlichia spp., Anaplasma spp., Hepatozoon spp. and Leishmania spp. in blood samples and ticks, collected from two dogs from Rio Grande do Norte showing suggestive tick-borne disease by using molecular techniques. DNA of E. canis, H. canis and L. infantum were detected in blood samples and R. sanguineus ticks collected from dogs. Among all samples analyzed, two showed the presence of multiple infections with E. canis, H. canis and L. infantum chagasi. Here we highlighted the need for molecular differential diagnosis in dogs showing nonspecific clinical signs.

Cães que apresentam diversas doenças transmitidas por vetores podem mostrar nenhum ou alguns sinais clínicos inespecíficos. Dependendo da fase da infecção, a confirmação dos agentes envolvidos é necessária. O presente estudo teve como objetivo detectar a presença de Babesia spp., Ehrlichia spp., Anaplasma spp., Hepatozoon spp. e Leishmania spp. em amostras de sangue e carrapatos, coletados em dois cães do Rio Grande do Norte. Esses animais apresentavam sinais clínicos sugestivos de doenças transmitidas por carrapatos, quando foram usadas técnicas moleculares. DNA de E. canis, H. canis e L. infantum foram detectados em amostras de sangue e carrapatos R. sanguineus coletados dos cães. Entre todas as amostras analisadas, duas mostraram a presença de infecções múltiplas por E. canis, H. canis e L. infantum chagasi. Destaca-se a necessidade de um diagnóstico molecular diferencial em cães com sinais clínicos inespecíficos.
Estudo da coinfecção por patógenos transmitidos por vetores em cães e carrapatos no Rio Grande do Norte, Brasil
Keywords: CVBDs; Co-infection; Ehrlichia canis; Hepatozoon canis; Leishmania infantum; Molecular diagnosis; DCTVs; Coinfecção; Ehrlichia canis; Hepatozoon canis; Leishmania infantum; Diagnóstico molecular